Benefits of thermosonication in orange juice whey drink processing. (January 2022) - Oliveira, Gabriella A.R.; Guimarães, Jonas T.; Ramos, Gustavo Luis P.A.; Esmerino, Erick A.; Pimentel, Tatiana C.; Neto, Roberto P.C.; Tavares, Maria Inês B.; Sobral, Louise A.; Souto, Felipe; Freitas, Monica Q.; Costa, Leonardo Emanuel O.; Cruz, Adriano G.
Abstract: This study aimed to evaluate the effect of short-time heat-treatment (HTST, 90 °C/20 s) and thermosonication (TS) at temperatures of 70, 80, and 90 °C (TS70, TS80, and TS90) on the quality parameters of orange juice whey drinks. Formulations with different orange juice/reconstituted whey proportions were subjected to sensory analysis, and the ideal formulation was established through survival analysis (31% whey, 69% orange juice). This formulation showed approval of 75% of the consumers, which is considered satisfactory. It was processed by HTST or TS and evaluated for the microbial counts, rheological parameters, color, physical properties (differential scanning calorimetry and time-domain nuclear magnetic resonance), volatile compounds, and bioactive compounds. TS-treated orange juice whey drinks showed a higher microbial inactivation (>1 log cfu/mL increase) and microbial stability during 21 days of storage (2.9, 4, and 1.1 log cfu/mL lower counts for aerobic mesophilic bacteria, yeasts and molds, and lactic acid bacteria, respectively). Furthermore, it showed higher antioxidant (>15% increase), anti-hypertensive (>24% increase), and anti-diabetic (>30% increase) activities and lowered ascorbic acid degradation (>8%). Finally, it showed lower viscosity (decreases in consistency index >46.9 Pa.s n ) and an improved volatile profile (presence of maltol and butanoic acid, ethyl ester). The effects were more pronounced at 80 and 90 °C. TS is a promising technology for treating orange juice whey drinks. Industrial relevance: Thermosonication can be used in the processing of orange juice whey drinks, resulting in better microbial inactivation, increased shelf-life, and improved functional properties and physical parameters compared to conventional processing. In this sense, this research's findings contribute to the utilization of non-conventional technologies by the dairy industry. Highlights: Thermosonication promoted higher microbial inactivation (>1 log cfu/mL increase) and improved the volatile profile (presence of maltol and butanoic acid, ethyl ester); Thermosonicated beverages had higher antioxidant (>15% increase), anti-hypertensive (> 24% increase) and antidiabetic activities (>30% increase); Thermosonication resulted in less consistent (decreases in consistency index >46.9 Pa.s n ) and more homogeneous beverages; Thermosonication at 90 °C provided better homogenization and rheological properties.